Lost in Shangri-La : Escape from a Hidden World - Zuckoff, Mitchell (London Harper Press, 2011)
Award-winning former Boston Globe reporter Mitchell Zuckoff unleashes the exhilarating, untold story of an extraordinary World War II rescue mission, where a plane crash in the South Pacific plunged a trio of U.S. military personnel into the jungle-clad land of New Guinea.
Keywords: Missing in action -- Search and rescue operations -- World War (1939-1945)